Murder beyond the grave [compact disc, unabridged] : true-crime thrillers - Patterson, James, 1947- (Hachette Audio, 2018)
True-crime thrillers as seen on Discovery's Murder Is Forever TV series. In Murder beyond the Grave, wealthy Stephen Small is held for ransom, buried in a box, with just forty-eight hours of oxygen. In Murder in Paradise, developers Jim and Bonnie Hood tour a rustic property they want to modernize, but the locals don't like rich outsiders changing their way of life. Soon everybody will discover just how to make a killing in real estate.